The Paradox of Smart Tourism: Does Technology Empower or Discourage Experience Sharing - Sari, Mareta Kemala; Lita, Ratni Prima; Lenggogeni, Sari; Ma'ruf, Ma'ruf (Journal of Applied Engineering and Technological Science (JAETS), 2025)
This study aimed to develop a model for showing the process of sharing memorable experiences created at tourists destinations or digital tourism supported by smart tourism technology (STT). A survey was conducted on 136 tourists who stayed in home-based accommodations and shared experiences on Instagram, which were later reposted by the destination's official Instagram account. In this study, a quantitative method was used, and the questions were addressed using the SMART PLS 4.1.0.9 tool. Furthermore, data were collected using a purposive sampling method from 136 visitors in West Sumatra who had completed their stay, shared experiences in the form of photos or videos on social media, and had posts reposted by the destination’s official account. The results showed that tourists tended to place greater importance on the emotions evoked by travel experiences compared to those arising from interaction with smart tourism technology (STT) services when evaluating overall happiness. Both theoretical insights and practical applications were further discussed.